Age and Sex Standardized Prevalence of Corneal Opacity and Its Determinants: Tehran Geriatric Eye Study (TGES) - Hassan Hashemi; Reza Pakzad; Mohamadreza Aghamirsalim; Abbasali Yekta; Mohammad Mehdi Sadoughi; Nima Norouzikhiabani; Abolfazl Jafarzadehpour; Roghayeh Esmaieli; Mehdi Khabazkhoob (Tehran University of Medical Sciences, 2022)
Background: We aimed to determine the age and sex standardized prevalence of corneal opacity and its determinants Methods: The Tehran Geriatric Eye Study (TGES) is a population-based cross-sectional study conducted on 3791 subjects aged above 60 yr in Tehran, Iran (2019) selected using stratified random cluster sampling. After sampling, all subjects underwent complete ophthalmic, optometric, and eye examinations. Results: The 3310 participated in the study, of whom the data of 3284 were analyzed. The age and sex standardized prevalence with 95% confidence interval (CI) of corneal opacity in at least one eye, both eyes, and one eye was 9.58% (95% CI: 8.50 to 10.79), 5.52% (95% CI: 4.71 to 6.45), and 4.07% (95% CI: 3.35 to 4.94), respectively. The mean uncorrected visual acuity (UCVA) and best-corrected visual acuity (BCVA) according to LogMar were worse in subjects with corneal opacity (both P<0.001). According to multiple logistic regression analysis, male sex (OR: 1.98; P: 0.003), age>80 yr (OR: 2.05; P: 0.004), and lack of insurance coverage (OR: 1.87; P: 0.004) increased the odds and high school education (OR: 0.68; P: 0.003) reduced the odds of corneal opacity. Among the study variables, sex was the most important determinant of corneal opacity (standardized beta: 0.126). Conclusion: This study found a high prevalence of corneal opacity in the geriatric population. Considering the increasing trend of population aging in Iran, attention should be paid to prioritizing public health policies to estimate resources required for providing comprehensive corneal services and improving geriatric eye health.